Impact of Ringer’s Solution Challenge Stress to Immunostimulatory Experiment, Insights From Japanese Flounder - Liu, Jinxiang; Li, Zan; Wang, Yujue; Zhang, Quanqi (Frontiers in Physiology, 2020)
Ringer’s or phosphate buffer saline (PBS) solution buffer usually was used as dilution butter in intraperitoneal injection. Stress could activate immune response, inflammatory response and glycogen metabolic process. The impact of solution buffer as a stressor to immune system was ignored in immunostimulatory experiment. In this report, we tested the hypothesis that the innate immune response and glycogen metabolic process were altered when it were challenged with Ringer’s in Japanese flounder (Paralichthys olivaceus). RNA-seq was performed after challenge with Ringer’s at 8 h and 48 h. The data revealed that the expression profiles of blood, gill and kidney were significantly changed. Differentially expressed genes (DEGs) were identified, and energy metabolic and immune-related genes were up-regulated or down-regulated obviously. GO and KEGG analyses showed that DEGs were mainly enriched in innate immune terms and pathways. Weighted gene co-expression networks analysis (WGCNA) also indicated the highest association module with stress. A total of 16 genes were detected in the grey module, which were immune-related and metabolic-related genes. These results provided fundamental information on intraperitoneal injection with solution buffer. It offered useful clues to further explore the functional mechanism of stress and immunity.